Developing a digital data collection platform to measure the prevalence of sepsis in Wales. (19th April 2016) - Sharif, B; Lundin, RM; Morgan, P; Hall, JE; Dhadda, A; Mann, C; Donoghue, D; Brownlow, E; Hill, F; Carr, G; Turley, H; Hassall, J; et al.
Abstract : Objective To develop a secure, efficient, and easy-to-use data collection platform to measure the prevalence of sepsis in Wales over 24 hours. Materials and Methods Open Data Kit was used on Android devices with Google App Engine and a digital data collection form. Results A total of 184 students participated in the study using 59 devices across 16 hospitals, 1198 datasets were submitted, and 97% of participants found the Open Data Kit form easy to use. Discussion We successfully demonstrated that by combining a reliable Android device, a free open-source data collection framework, a scalable cloud-based server, and a team of 184 medical students, we can deliver a low-cost, highly reliable platform that requires little training or maintenance, providing results immediately on completion of data collection. Conclusion Our platform allowed us to measure, for the first time, the prevalence of sepsis in Wales over 24 hours.